Value Clarification Technique Learning Model Based on Folklore towards Knowledge Competence of Civic Education - Wiradewi, Ni Made; Sri Asri, I G. A. Agung; Manuaba, Ida Bagus Surya (Jurnal Ilmiah Sekolah Dasar, 2020)
The low competence of civic education knowledge due to less optimal use of models when learning resulted that students have difficulty understanding learning and getting bored quickly. This study aimed to analyze the effect of the Value Clarification Technique learning model based on the civic on the knowledge competence of civic education. This study was a quasi-experimental research with nonequivalent control group design. A total of 184 students from 6th grade IV became the population. Samples were selected using a random sampling technique. Knowledge competence of civic education data collection used multiple-choice objective test instruments. The data obtained were analyzed using a t-test, namely polled variance. The results of data analysis obtained t-count = 2.880> t-table = 2.005 at a significance level of 5% with dk = n1 + n2-2 so that Ho is rejected and Ha is accepted. Then it can be concluded that there is a significant effect in the knowledge competence of civic education between students who are taught the Value Clarification Technique learning model based on the folklore.